Observational Evidence of Large‐Scale Multiple Reconnection at the Earth's Dayside Magnetopause. Issue 10 (27th October 2018) - Fuselier, S. A.; Petrinec, S. M.; Trattner, K. J.; Broll, J. M.; Burch, J. L.; Giles, B. L.; Strangeway, R. J.; Russell, C. T.; Lavraud, B.; Øieroset, M.; Torbert, R. B.; Farrugia, C. J.; et al.
Abstract: Magnetic flux ropes of various scale sizes have been observed at the Earth's magnetopause for four decades. These multiple structures resulting from reconnection have complex internal field and plasma signatures, and evolve as they propagate along the dayside magnetopause. Here plasma and magnetic field observations from the Magnetospheric Multiscale (MMS) mission are used to describe a different type of large‐scale multiple reconnection, magnetic flux rope‐like structure at the Earth's magnetopause. These observations show at least two X lines separated by many Earth radii. Unlike smaller‐scale flux ropes or flux transfer events, these multiple X lines are stationary and consist of primary and secondary X lines. The secondary X line is either transient in time or does not reconnect all of the magnetic flux that reconnects at the primary X line. Several examples of these large‐scale reconnection structures are tabulated. These examples indicate that this type of structure may be common at the magnetopause at least for a narrow range of interplanetary magnetic field clock angles. Plain Language Summary: Magnetic reconnection at the Earth's magnetopause is the driver for the interaction between the solar wind and Earth, that is, space weather. This reconnection is usually considered to occur along a long reconnection X line across the magnetopause. However, the observations here show that there are multiple X lines at the magnetopause where reconnection is occurring. These X lines do not appear to move and there appears to be a primary X line and at least one secondary X line. Key Points: Multiple reconnection X lines are observed at the Earth's magnetopause Their particle signatures indicate that the X lines are quasi‐stationary and far apart from one another